Triazole‐Tailored Guanosine Dinucleosides as Biomimetic Ion Channels to Modulate Transmembrane Potential. Issue 11 (20th February 2014) - Kumar, Y. Pavan; Das, Rabindra Nath; Kumar, Sonu; Schütte, Ole Mathis; Steinem, Claudia; Dash, Jyotirmayee
Abstract A "click" ion channel platform has been established by employing a clickable guanosine azide or alkyne with covalent spacers. The resulting guanosine derivatives modulated the traffic of ions across the phospholipid bilayer, exhibiting a variation in conductance spanning three orders of magnitude (pS to nS). Förster resonance energy transfer studies of the dansyl fluorophore with the membrane binding fluorophore Nile red revealed that the dansyl fluorophore is deeply embedded in the phospholipid bilayer. Complementary cytosine can inhibit the conductance of the supramolecular guanosine channels in the phospholipid bilayers.